Unique TCR loci architecture in newts: TRA and TRD separation in Pleurodeles waltl - Migalska, Magdalena; Babik, Wiesław (Frontiers in Immunology, 2025)
T cell receptors (TCRs) are central components of the adaptive immune system, yet the genomic organization of TCR-encoding loci is highly complex and has been fully characterized in only a handful of vertebrate taxa. Many important lineages remain largely uncharted, with notable gaps in ectothermic groups. This gap is especially pronounced in amphibians, particularly salamanders (Urodela), where enormous genome sizes have long hindered the availability of high-quality reference sequences. Here, using a recently published chromosome-scale, haplotype-resolved genome of the Iberian ribbed newt, Pleurodeles waltl, we report the first comprehensive characterization of all four TCR loci (TRA, TRB, TRG, and TRD) in this species. P. waltl, alongside the axolotl, is an emerging urodele model, particularly in regenerative biology. Strikingly, we found that the TRA and TRD loci reside on separate chromosomes—a genomic configuration not previously reported in any jawed vertebrate. This unusual organization was confirmed in related species, suggesting it represents an ancestral feature of newts. Moreover, a more recent duplication gave rise to two distinct TRA loci located on two separate chromosomes. Furthermore, using our high-quality genomic TCR reference, we conducted a proof-of-concept TCR repertoire analysis and examined TCR expression through ontogeny in a series of RNA-seq experiments. The genomic toolkit established here paves the way for in-depth studies of TCR diversity in P. waltl, strengthening its position as a model species in amphibian immunology.